The Legal Responsibility of the Land Seller to the Buyer Who Suffers Losses Due to the Delay in Transferring Land Rights Based on Government Regulation Number 24 of 1997 (Study of Case Decision Number 711/Pdt.G/2023/PN JKT. UTR - Aritonang, Anggi Asyera; Siregar, Hisar; Simamora, Sovia Febrina Tamaulina (PT FORMOSA CENDEKIA GLOBAL, 2025)
The transfer of land rights is an important aspect of the sale and purchase transaction to ensure legal certainty for the buyer. However, there are often delays due to the seller's negligence that causes losses. This study aims to analyze the seller's legal responsibility to the buyer in the case of delay in the transfer of rights based on Government Regulation No. 24 of 1997, as well as to examine the judge's considerations in Decision Number 711/Pdt.G/2023/PN Jkt.Utr. The research method used is normative juridical with a case study approach. The results show that sellers remain legally liable for delays despite administrative constraints, and courts provide legal protection to good-faith buyers. This decision affirms the principles of legal certainty, justice, and protection for the aggrieved party.